2013
DOI: 10.1017/dmp.2013.22
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder in Parents and Youth After Health-Related Disasters

Abstract: These findings indicate that pandemic disasters and subsequent disease-containment responses may create a condition that families and children find traumatic. Because pandemic disasters are unique and do not include congregate sites for prolonged support and recovery, they require specific response strategies to ensure the behavioral health needs of children and families. Pandemic planning must address these needs and disease-containment measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
876
6
69

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,017 publications
(1,048 citation statements)
references
References 19 publications
40
876
6
69
Order By: Relevance
“…Five studies compared psychological outcomes for people quarantined with those not quarantined. 9,19,27,28,33 A study 9 of hospital staff who might have come into contact with SARS found that immediately after the quarantine period (9 days) ended, having been quarantined was the factor most predictive of symptoms of acute stress disorder. In the same study, quarantined staff were significantly more likely to report exhaustion, detachment from others, anxiety when dealing with febrile patients, irritability, insomnia, poor concentration and indecisiveness, deteri orating work performance, and reluctance to work or consid eration of resignation.…”
Section: The Psychological Impact Of Quarantinementioning
confidence: 99%
See 1 more Smart Citation
“…Five studies compared psychological outcomes for people quarantined with those not quarantined. 9,19,27,28,33 A study 9 of hospital staff who might have come into contact with SARS found that immediately after the quarantine period (9 days) ended, having been quarantined was the factor most predictive of symptoms of acute stress disorder. In the same study, quarantined staff were significantly more likely to report exhaustion, detachment from others, anxiety when dealing with febrile patients, irritability, insomnia, poor concentration and indecisiveness, deteri orating work performance, and reluctance to work or consid eration of resignation.…”
Section: The Psychological Impact Of Quarantinementioning
confidence: 99%
“…Approximately 34% (938 of 2760) of horse owners quarantined for several weeks because of an equine influenza outbreak reported high psychological distress during the outbreak, compared with around 12% in the Australian general population. 28 A study 27 comparing posttraumatic stress symptoms in parents and children quarantined with those not quarantined found that the mean posttraumatic stress scores were four times higher in children who had been quarantined than in those who were not quarantined. 28% (27 of 98) of parents quarantined in this study reported sufficient symptoms to warrant a diagnosis of a traumarelated mental health disorder, compared with 6% (17 of 299) of parents who were not quarantined.…”
Section: The Psychological Impact Of Quarantinementioning
confidence: 99%
“…30% of the children who were isolated or quarantined met the clinical criteria for post-traumatic stress disorder. 5 Furthermore, separation from parents or parental loss during childhood also has long-term adverse effects on mental health, including a higher risk of developing mood disorders and psychosis, and death by suicide in adulthood. 6,7 The age of the initial separation is known to be relevant to psychological development.…”
Section: Mental Health Considerations For Children Quarantined Becausmentioning
confidence: 99%
“…The anticipated shortfall in vaccine supply is 29 million doses (of the 40 million needed), which resulted in a delay in vaccine introduction to countries currently without the human papillomavirus vaccine, with more delays expected in 2020. 5 Constraints on vaccine supply are anticipated to last until the mid-2020s; however, the extent and duration of the shortfall are highly dependent on the vaccination strategies for human papillomavirus that are implemented worldwide. For more on the commitment see https://www.who.int/ reproductivehealth/call-toaction-elimination-cervicalcancer/en/…”
Section: Prioritisation Of the Human Papillomavirus Vaccine In A Timementioning
confidence: 99%
“…o u r n a l P r e -p r o o f des sujets confinĂ©s en comparaison de 7 % chez ceux qui n'Ă©taient pas confinĂ©s(79).Hawryluck et al ont observĂ© 29 % de symptĂŽmes modĂ©rĂ©s de stress post-traumatique en sortie de confinement liĂ© au SARS(80). De la mĂȘme maniĂšre, un SSPT a Ă©tĂ© observĂ© chez des personnels des hĂŽpitaux confinĂ©s jusqu'Ă  3 ans aprĂšs l'Ă©pidĂ©mie de SARS en Chine(81).…”
unclassified